Effects of High Phytase Supplementation in Lactation Diets on Sow and Litter Performance - K. L. Batson; H. Calderon Cartagena; R. D. Goodband; J. C. Woodworth; M. D. Tokach; S. S. Dritz; J. M. DeRouchey (Kansas Agricultural Experiment Station Research Reports, 2019)
A total of 109 sows (Line 241; DNA, Columbus, NE) were used in a study to evaluate the effect of increasing phytase concentration in lactating sow diets on farrowing duration, and sow and litter performance. On d 107 of gestation, sows were blocked by body weight and parity and allotted to 1 of 3 dietary treatments of increasing phytase concentration (0, 1,000, or 3,000 FTU/kg; Ronozyme HiPhos 2700; DSM Nutritional Products, Inc., Parsippany, NJ). The control diet contained no phytase and was formulated to contain 0.50% standardized total tract digestible phosphorus (STTD P; 0.45% available P) and 0.62% STTD calcium (0.90% total Ca). The phytase diets contained 1,000 or 3,000 FTU/kg also formulated to 0.50% STTD P and 0.62% STTD Ca including the release of 0.132 STTD P and 0.094 STTD Ca in both phytase diets. Diets were balanced for net energy by altering choice white grease. Diets were fed from d 107 of gestation until weaning (d 17 ± 2) and all farrowings were monitored with farrowing duration measured starting at the time the first pig was born until the first dispersal of placental tissues with no subsequent pigs born. Litters were cross-fostered within treatment until 48 h post-farrowing to equalize litter size. There were no differences among treatments in body weight at d 107 of gestation, 24 h after farrowing, or at weaning. Sow average daily feed intake (ADFI) from farrowing to weaning tended to increase (linear,P= 0.093) as phytase units increased. There was no evidence for difference in farrowing performance, wean-to-estrus interval, or litter size among dietary treatments. Although not significant (linear,P= 0.226), farrowing duration decreased for sows fed 3,000 FTU/kg. Litter weaning weight increased (quadratic,P= 0.039) and overall litter gain increased (quadratic,P= 0.047) with 1,000 FTU of phytase. In summary, sow feed intake tended to increase linearly with increasing phytase; however, feeding 1,000 FTU/kg maximized overall litter gain and weaning weight. Farrowing duration was numerically decreased with increasing units of phytase. This small-scale study presents interesting impacts on sow and litter performance due to high inclusions of dietary phytase; however, a commercial trial with more sows is warranted.
Keywords: farrowing duration; lactation; phytase; sow